LIABILITY OF ADVERTISING COMPANIES FOR CONSUMER LOSSES RESULTING FROM MISLEADING ADVERTISEMENTS - Adila, Arina Hukmu; Adhi, Yuli Prasetyo (SYNTIFIC, 2025)
Background. The increasing number of cases involving advertising installation companies that neglect safety standards has raised significant legal concerns, particularly regarding consumer protection. The background of this study lies in the unlawful acts committed by such companies, which often result in physical, material, or psychological harm to the public. This research aimed to determine the extent of the responsibility of advertising companies in committing unlawful acts and analyze the legal liability for unlawful acts by advertising companies that result in consumer harm. Research Method. This research uses a normative juridical method with a statutory and conceptual approach. Legal materials were sourced from primary legal norms, such as the Indonesian Civil Code, especially Article 1365 and supported by secondary sources, including academic literature and expert interpretations. The analysis was conducted qualitatively by classifying legal principles, doctrines, and case examples. Findings. The findings indicate that unlawful acts, as defined in Article 1365 of the Civil Code, are interpreted broadly in Indonesia. These acts may include violations of others' rights, neglect of legal obligations, conduct contrary to public decency, and actions against societal norms of caution. Advertising companies that disregard structural safety, proper licensing, or installation procedures can be held civilly liable if their actions cause harm to others. Conclusions. Advertising installation companies bear full legal responsibility for any consumer harm resulting from their unlawful conduct. To ensure accountability, stronger regulatory oversight and enforcement mechanisms are needed to protect the rights and safety of the public.